2003
DOI: 10.1002/mpo.10284
|View full text |Cite
|
Sign up to set email alerts
|

Tube feeding and bone marrow transplantation

Abstract: TF is possible and equal in efficacy to PN in children undergoing BMT, and may have budgetary benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 20 publications
6
34
0
1
Order By: Relevance
“…10,14 It should be noted that patients in the EN-PN group patients tended to be older than the others, suggesting that teenagers are reluctant to embark on such a regimen. In the Hopman study, 13 tolerance was significantly better in younger patients (mean age 3.3 vs 8 years of age). During the pre-transplant interview, emphasis was placed on EN as being a recommended essential treatment.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…10,14 It should be noted that patients in the EN-PN group patients tended to be older than the others, suggesting that teenagers are reluctant to embark on such a regimen. In the Hopman study, 13 tolerance was significantly better in younger patients (mean age 3.3 vs 8 years of age). During the pre-transplant interview, emphasis was placed on EN as being a recommended essential treatment.…”
Section: Discussionmentioning
confidence: 89%
“…19 Therefore, Szeluga et al 15 conducted a randomised trial comparing 31 PN with 30 EN cases in allo-and auto-SCT patients above 10 years of age; they concluded that PN was no more effective than EN, and suggested that it should be reserved for patients demonstrating intolerance to EN. Three paediatric studies concluded that EN was an effective nutritional support in SCT: Langdana et al 10 and Papadopoulou et al 12 studied EN (49 and 21 patients, respectively) in both allo-and auto-SCT children, while Hopman et al 13 compared 12 EN vs 22 PN cases in allo-SCT children. However, most studies included only a small number of patients or a heterogeneous patient population of paediatric and adult patients with solid tumours, haematological malignancies, and both auto-and allo-SCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 However, nutritional status in these studies was assessed using anthropometric methods, which may have limitations when used in children with clinical conditions. In this paper, nutritional status is represented using body cell mass (BCM).…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Previous studies have reported that children pre-HSCT are generally well nourished as a group according to anthropometric measures; however, there can be a large variation in nutritional status. 10,11 The importance of optimal nutritional status pre-transplant is imperative as there is reduced opportunity to provide appropriate nutritional support during and post transplant owing to the intensity of conditioning regimes, mucositis and the possibility of graft vs host disease resulting in poor functional integrity of the gastrointestinal tract. 12 In view of the potential link between nutritional status and survival in pediatric HSCT patients and the lack of studies that have investigated this relationship, the aim of this study is to investigate the association between nutritional status pre-HSCT and survival in a pediatric population.…”
Section: Introductionmentioning
confidence: 99%